Pengaruh Deforestasi dan Upaya Menjaga Kelestarian Hutan di Indonesia - Clearestha Nakita; Fatma Ulfatun Najicha (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
Forests have many benefits for human life and the environment. Forests are also a place to live for various species of plants and animals. Forest management in Indonesia has been regulated in legal regulations such as the 1945 Constitution of the Republic of Indonesia up to statutory regulations. However, in reality there are still activities that lead to forest destruction. This study aims to examine the legal regulations in Indonesia in regulating forest management, the reality that occurs, and efforts to preserve Indonesia's forests. The type of research used by the author is normative legal research which aims to examine the legal aspects related to legal arrangements in Indonesia in regulating forest management. Forest and environmental management have been regulated in legal regulations. Both in the 1945 Constitution of the Republic of Indonesia to other laws and regulations. The existence of this legal arrangement is an effort to maintain and improve order and ensure legal certainty. Because the impact of this deforestation causes the loss of tropical rain forest cover which is a habitat for animals and plants.